The Role of Husbands in Fostering Harmony in Their Households with Career Wives - Jamilah; Ahmad, Sabarudin; Emzaed, Ali Murtadho (Jurnal Ilmu Hukum Tambun Bungai, 2025)
Indonesia's social and economic developments over the past four years have shown significant dynamics in gender relations within the family. The increasing number of career women participating in public and private sectors requires a paradigm shift in the husband's role from an authoritative figure to an equal partner in domestic life. This shift has given rise to the notion of husbands who actively participate in childcare, household responsibilities, and professional support for their wives. This study analyzes the role of husbands in maintaining harmonious family relationships with career women from a Human Rights (HAM) perspective, emphasizing the principles of equality, dignity, and shared responsibility. This research employs a qualitative socio-legal method combined with normative analysis. Data were drawn from observations of everyday family interactions among civil servants and young professional households, as well as an examination of national and international human rights instruments, including the ICCPR, CEDAW, and Law No. 39 of 1999. These observations highlight concrete forms of gender equality for example, shared decision making, division of domestic labor, and emotional support that reduces work family conflict. The findings show that the husband's active involvement not only strengthens gender equality and minimizes domestic tension but also reflects the practical implementation of non-discrimination and equal partnership within family life. Thus, the role of the husband becomes a tangible manifestation of human rights values in the domestic sphere, positioning the family as the primary setting for cultivating justice, equality, and respect for human dignity.